1959
DOI: 10.1001/archneur.1959.03840020022004
|View full text |Cite
|
Sign up to set email alerts
|

The Transcerebral Venous System

Abstract: In a long-term study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…[7][8][9][10] Superficial veins are small short vessels that originate 1-2 cm below gray matter, run in a ventricolofugal way through the cortical layer, and drain into superficial pial veins. DMVs are longer and larger vessels that originate in the subcortical WM in the same areas as superficial veins, run in a ventricolopetal way to the ventricular surface, and drain into subependymal veins.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Superficial veins are small short vessels that originate 1-2 cm below gray matter, run in a ventricolofugal way through the cortical layer, and drain into superficial pial veins. DMVs are longer and larger vessels that originate in the subcortical WM in the same areas as superficial veins, run in a ventricolopetal way to the ventricular surface, and drain into subependymal veins.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Anatomic studies with use of postmortem vascular injections have made extensive contributions to our understanding of the cerebral venous drainage system. [10][11][12] The venous drainage of the cerebral hemispheres is divided into the superficial and the deep systems. The superficial system consists of the SSS, the transverse sinuses, torcular, sigmoid sinuses, and the internal jugular veins.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, the veins of the lateral surface of the occipital lobe join the transverse sinus. 12 The deep (Galen) venous system includes the basal vein of Rosenthal and the internal cerebral veins 14,15 (Fig 3). It has been reported that there is no correlation between the location and the size of the brain lesions and the site and extent of the sinus thrombosis in adult patients, suggesting that adults might better tolerate CSVT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cortical venous system, such as the vein of Labbe and the transcerebral venous system, [18] might partially explain the excellent result in our patient. Moreover, DSA suggested the blood from SSS was drained to transverse sinus and sigmoid sinus via superior and inferior anastomotic veins and those collateralized venous outflows were located anterior to the wound site.…”
Section: Discussionmentioning
confidence: 92%